Calvarial ectopic meningothelial meningioma - Vital, Roberto Bezerra [UNESP]; Hamamoto Filho, Pedro Tadao [UNESP]; Lapate, Renan Luiz [UNESP]; Martins, Vinícius Zanin [UNESP]; de Oliveira Lima, Flávio [UNESP]; Romero, Flávio Ramalho [UNESP]; Zanini, Marco Antônio [UNESP] (Elsevier B. V., 2015)
Meningiomas are the most common benign neoplasm of the brain whereas ectopic presentation, although reported, is rare. Among these ectopic tumors, there are a group of purely intraosseous meningiomas, which usually are diagnosed differentially from common primary osseous tumor such as fibrous dysplasia and osteoid osteoma. We report a 62-year-old female with a history of headaches and 6 months of progressive right parietal bulging, with no neurological signs. Parietal craniotomy was performed with immediate titanium cranioplasty of the parietal convexity. Histopathology exams revealed an ectopic intradiploic meningioma without invasion of cortical layers, with positive staining for progesterone receptors and epithelial membrane antigen. Ectopic intraosseous meningiomas remain a rare neoplasm with only a few cases reported. The main theories to justify the unusual topography appear to be embryological remains of neuroectodermal tissue or cellular dedifferentiation. Surgical treatment seems the best curative option.
Keywords: Benign; Brain tumor; Meningioma